2018
DOI: 10.1021/acs.chemmater.8b03827
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electrochemical, and Thermal Properties of Nickel-Rich LiNixMnyCozO2 Materials

Abstract: Nickel-rich LiNi x Mn y Co z O 2 materials (x + y + z = 1, x ≥ 0.6) (NMC) are one of the most promising positive electrode candidates for lithium-ion cells due to their high specific capacity, ease of production, and moderate cost. Conventional NMC materials such as LiNi 0.4 Mn 0.4 Co 0.2 O 2 (NMC442), LiNi 0 . 5 Mn 0 . 3 Co 0 . 2 O 2 (NMC532), Li-Ni 0.6 Mn 0.2 Co 0.2 O 2 (NMC622), etc. have 20% of costly Co among the transition metal atoms. To lower the Co content while maintaining good electrochemical perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 28 publications
5
91
0
Order By: Relevance
“…Moreover, researchers reported that cation disorder can lower spacing between atomic layers in the lattice of the NMC-based cathodes, hinder Li + movement and reduce the amount of active Ni and Li [53]. In the case of higher Ni percentage cathodes, Mn 4+ can partially be replaced by Ni, which increases the valence of Ni and therefore lowers the possibility of Ni atoms migrating to 3a sites [8]. However, because the total amount of Ni also increases, Ni 2+ migration still occurs to a larger extent.…”
Section: Surface Reconstruction To Fm3m Rocksaltmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, researchers reported that cation disorder can lower spacing between atomic layers in the lattice of the NMC-based cathodes, hinder Li + movement and reduce the amount of active Ni and Li [53]. In the case of higher Ni percentage cathodes, Mn 4+ can partially be replaced by Ni, which increases the valence of Ni and therefore lowers the possibility of Ni atoms migrating to 3a sites [8]. However, because the total amount of Ni also increases, Ni 2+ migration still occurs to a larger extent.…”
Section: Surface Reconstruction To Fm3m Rocksaltmentioning
confidence: 99%
“…Accelerating rate calorimetry (ARC) is another method adopted by researchers to measure self-heating rates (SHRs) versus temperature [8,142]. For example, in the comparison of the SHR of 4 types of Ni-rich NMC-based cathodes (Fig.…”
Section: Thermal Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…a) Contour plot of percent Ni in the Li layer as a function of Ni content and Co content. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Origins Of Surface/interface Structure Degradationmentioning
confidence: 99%